The applications of the partial Hamiltonian approach to mechanics and other areas. (November 2016) - Naz, R.
Abstract: The partial Hamiltonian systems of the form q ̇ i = ∂ H ∂ p i, p ̇ i = − ∂ H ∂ q i + Γ i ( t, q i, p i ) arise widely in different fields of the applied mathematics. The partial Hamiltonian systems appear for a mechanical system with non-holonomic nonlinear constraints and non-potential generalized forces. In dynamic optimization problems of economic growth theory involving a non-zero discount factor the partial Hamiltonian systems arise and are known as a current value Hamiltonian systems. It is shown that the partial Hamiltonian approach proposed earlier for the current value Hamiltonian systems arising in economic growth theory Naz et al. (2014)[1] is applicable to mechanics and other areas as well. The partial Hamiltonian approach is utilized to construct first integrals and closed form solutions of optimal growth model with environmental asset, equations of motion for a mechanical system with non-potential forces, the force-free Duffing Van der Pol Oscillator and Lotka–Volterra models. Abstract : Highlights: Partial Hamiltonian systems arise widely in different fields of the applied mathematics. Partial Hamiltonian approach is applicable to mechanics and other areas as well. This approach yields a systematic way to derive first integrals of mechanical systems with external forces.